Cellular Automaton Simulation of Tumour Growth – Equivocal Relationships between Simulation Parameters and Morphologic Pattern Features - Josef Smolle (Analytical Cellular Pathology)
Objective: To develop an interpretation procedure which estimates simulation parameters (tumour cell motility, tumour cell adhesion, autocrine and paracrine growth control, stroma destruction) of simulated patterns solely based on morphometric features of the morphologic pattern.